2009
DOI: 10.1007/s10591-009-9083-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Trauma and Pregnancy: A Qualitative Exploration of Women’s Dual Life Experience

Abstract: Using a qualitative methodology, we investigated the possible connection between pregnant females' past sexual trauma experiences and current experiences of pregnancy. Semi-structured interviews were conducted during the third trimester of pregnancy with ten expectant mothers with self-reported histories of sexual trauma. Participants were asked to describe their past sexual trauma experience, current maternity experience, and any relationship or connection between these life experiences. Four dominant categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(61 citation statements)
references
References 31 publications
0
61
0
Order By: Relevance
“…As this study and past research have demonstrated, survivors’ pasts can haunt them throughout pregnancy and childbirth. The physical and psychological adaptations of pregnancy can be especially difficult for survivors . Survivors stand to benefit from having support and remaining in control of their childbearing experience.…”
Section: Resultsmentioning
confidence: 99%
“…As this study and past research have demonstrated, survivors’ pasts can haunt them throughout pregnancy and childbirth. The physical and psychological adaptations of pregnancy can be especially difficult for survivors . Survivors stand to benefit from having support and remaining in control of their childbearing experience.…”
Section: Resultsmentioning
confidence: 99%
“…drug taking). Pregnancy generated hope for the future (Chase et al, 2009;Schwerdtfeger & Wampler, 2009;Pryce & Samuels, 2010;O"Mahen et al, 2011). The responsibility of pregnancy was seen in a positive light, stimulating self-caring and protective behaviour (Armstrong & Pooley, 2005;Chase et al, 2009;Maxwell, Proctor & Hammond, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy placed physical limits upon them, and some reported feeling isolated from social support. Women who had experienced past sexual trauma described pregnancy as representing a new life, beginning, direction and hope (Schwerdtfeger & Wampler, 2009). Some felt proud about carrying their partner"s child.…”
Section: Introductionmentioning
confidence: 99%
“…Half of the studies (n=5) focused specifically on survivors of childhood sexual abuse (Coles & Jones, 2009;Montgomery, Pope, & Rogers, 2015a, 2015bParratt, 1994;Rhodes & Hutchinson, 1994;Roller, 2011). Four studies focused on survivors of sexual trauma (Burian, 1995;Halvorsen, Nerum, Oian, & Sørlie, 2013;LoGiudice & Beck, 2016;Schwerdtfeger & Wampler, 2009). Only one study focused on women with both a history of childhood sexual abuse and with abuse-related posttraumatic stress (Seng, Sparbel, Low, & Killion, 2002).…”
Section: Review Resultsmentioning
confidence: 99%
“…A woman's childbearing experience can be negatively affected by a fear-mediated response caused by past trauma (Heimstad, Dahloe, Laache, Skogvoll, & Schei, 2006;Schwerdtfeger & Wampler, 2009). Research in this area has demonstrated that women who have experienced sexual abuse have higher stress levels and are at greater risk for preterm birth and more difficult pregnancies and childbirth experiences than their counterparts (Benedict, Paine, Paine, Brandt, & Stallings, 1999;Jacobs, 1992;Leeners, Rath, Block, Görres, & Tschudin, 2014).…”
Section: Introductionmentioning
confidence: 99%